DIALOG ANTAR AKTOR DALAM IMPLEMENTASI KEBIJAKAN PERATURAN GUBERNUR No. 30 TAHUN 2011 TENTANG PEDOMAN PENGELOLAAN CSR/PKBL DI PROVINSI LAMPUNG - , SYAIFULLAH NOER ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is based on phenomena of the hardest of implementation of the policy, many several of the problems that occurred because of the failure implementation of the policy. In Lampung Province there is a policy made by Government of Lampung Province. This policy becomes manual for all of entrepreneur in order to go through CSR program which is synergy with the program of region development. In reality this policy becomes wrapped around the government, private and society. The dynamic of differences interest and perception between them become serious problem for implemented this regulation or this policy. By mean of the dialogue, this research try to describe detailed the interaction that could happened among the actors along implemented the policy of Governor Regulation No. 30 Year 2011. This research supposed to understand the actors who mixed up with process implementation of the policy within many interest and perception in order to know the kind of the dialogue in the policy of implementation Governor No. 30 Year 2011. Also to know the obedience the company go through the CSR Program, both of the company whose become the objective of the research are